Valorization of Pennisetum purpureum (Elephant grass) and piggery manure for energy generation. (15th October 2021) - Ojediran, O.J.; Dahunsi, S.O.; Aderibigbe, V.; Abolusoro, S.; Adesulu-Dahunsi, A.T.; Odekanle, E.L.; Odejobi, O.J.; Ibikunle, R.A.; Ogunwole, J.O.
Highlights: Energy generation from Elephant grass (El-g) and piggery manure (PM) was evaluated. Elephant grass and piggery manure were found to be rich in elemental compositions. Alkaline pretreatment enhanced the valorization of Elephant grass. A total of 409.5 m 3 CH4 /kg VS was obtained from the pretreated El-g + PM. An average of 11.07 m 3 CH4 /kg VS/day was obtained. Abstract: This study investigated the biogas production potential of Pennisetum purpureum (Elephant grass) (El-g) co-digested with piggery manure (PM) under mesophilic condition in order to combat the menace of weed in cropping systems as well as pollution problems emanating from disposal of PM. Prior to anaerobic digestion (AD), El-g was subjected to a combination of mechanical, thermal and alkaline pretreatments. Using cattle rumen content as inoculum, the pretreated El-g was anaerobically co-digested with PM while the raw El-g was also co-digested with PM and served as control experiment. The physicochemical characteristics of feedstock were evaluated before and after the digestion period using standard methods. The initial high concentrations of chemical oxygen demand (COD) reduced significantly after digestion indicating efficiency of the digestion process. Also, there were reductions in concentrations of calcium and other parameter needed for microbial growth after the digestion which indicated their utilization by microbes to generate biogas. Biogas production began on the 5th and 7th days and was progressive until 30th and 24th days in both digestions after which a decline was observed until the end of the experiment. For the digestion period of 37 days, the total biogas recorded from the pretreated and untreated experiments were 409.5 and 184.1 m 3 CH4 /kg VS with average of 11.07 and 4.98 m 3 CH4 /kg VS/day respectively. The study concluded that co-digestion with piggery dung enhanced the biogas producing capacity of El-g hence advocated.